Alcohol dehydrogenases from Proteus mirabilis contribute to alcoholic flavor. (18th March 2019) - Yu, Fengchuan; Bai, Yajun; Fan, Tai‐ping; Zheng, Xiaohui; Cai, Yujie
Abstract: BACKGROUND: Cheese ripening involves a complex series of metabolic reactions and numerous concomitant secondary transformations. Alcohol dehydrogenase (ADH) converts aldehydes into their corresponding alcohols, which enrich cheese aroma. RESULTS: In this study, we identified five ADH genes in Proteus mirabilis JN458, and these genes were overexpressed and characterized in Escherichia coli BL21 (DE3). The optimum pH was 7.0 for the purified recombinant ADH‐1, ADH‐2, and ADH‐3 and 8.0 for ADH‐4 and ADH‐5. The optimum temperature was 40 °C for ADH‐1, ADH‐3, and ADH‐5 and 45 °C for ADH‐2 and ADH‐4. The K m value of ADH‐1, ADH‐2, and ADH‐3 was 34.45, 16.90, and 10.01 µmol L −1 for phenylacetaldehyde, respectively. The K m value of ADH‐4 and ADH‐5 was 14.81 and 24.62 µmol L −1 for 2‐methylbutanal, respectively. CONCLUSION: Proteus species play important roles during cheese ripening. The results of our study are important for further research on cheese flavor and for quality control during cheese production. © 2019 Society of Chemical Industry